How one-to one E-learning enhances and affects high school students’ learning performance in the UAE - Al-Kendi Salem, Fatima Mohammed (2010)
The one-to-one E-learning solution has become a significant tool of 21st century teaching art within UAE. It also has become the language that UAE youth speak. Therefore, this paper discusses how this new injected solution affected and enhanced high school student learning performance based on a case study of the first high school in UAE which implemented this kind of solution for their students from K-10 through K-12. The paper also displays how students in high school age are attracted to such a way of learning, that transferred them from the old fashion learning environment where student needs to come early to the class and sit all the day listening to what teachers say, to a more motivated and energetic learning environment.Furthermore, the way teachers participated in implementing such a solution by designing affected curriculum for the students that is integrated and fit within one-to-one solution, added valuable value to the teaching process and gave more confidence to the teachers, because they consider themselves part of it. However, teachers need to be engaged in curriculum design of one-to-one E-learning solution, because from the daily interaction with students they can extract creative curriculum to student. Moreover, such a learning solution needs the maximum support from the management in financial, educational and technical side in order to succeed. Finally, more studies need to be conducted on the influence of the usage of one-to-one solution of E-learning on teachers’ expectations and how such a solution affect teachers career of opportunities and chances.